Lay piety and religious discipline in Middle English literature - Rice, Nicole R., 1973- (Cambridge ; New York : Cambridge University Press, 2008)
An examination of spiritual discipline, religious identity, and orthodoxy in Langland and Chaucer.
Cover; Half-title; Series-title; Title; Copyright; Dedication; Contents; Preface; Acknowledgments; Abbreviations; Introduction; Chapter 1 Translations of the cloister: regulating spiritual aspiration; Chapter 2 Dialogic form and clerical understanding; Chapter 3 Lordship, pastoral care, and the order of charity; Chapter 4 Clerical widows and the reform of preaching; Conclusion Spiritual guides in fifteenth-century books: cultural change and continuity; Notes; Bibliography; Index
Includes bibliographical references (pages 217-234) and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: English prose literature -- Middle English, 1100-1500 -- History and criticism; English poetry -- Middle English, 1100-1500 -- History and criticism; Religion and literature -- England -- History -- To 1500.; Spiritual life in literature; Spiritual life -- Christianity -- History of doctrines -- Middle Ages, 600-1500.; Religious thought -- Middle Ages, 600-1500.; Prose anglaise -- 1100-1500 (Moyen anglais) -- Histoire et critique; Poésie anglaise -- 1100-1500 (Moyen anglais) -- Histoire et critique; Vie spirituelle dans la littérature.; Pensée religieuse -- 600-1500 (Moyen Âge); LITERARY CRITICISM -- European -- English, Irish, Scottish, Welsh; English poetry -- Middle English; English prose literature -- Middle English; Religion and literature; Religious thought -- Middle Ages; Spiritual life -- Christianity -- History of doctrines -- Middle Ages; Spiritual life in literature; England; Mittelenglisch; Literatur; Religiöses Leben; Frömmigkeit; Disziplin; To 1500; Criticism, interpretation, etc; History